2021
DOI: 10.12688/wellcomeopenres.16577.2
|View full text |Cite
|
Sign up to set email alerts
|

Rapid inactivation of SARS-CoV-2 by titanium dioxide surface coating

Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) transmission occurs via airborne droplets and surface contamination. Titanium dioxide (TiO2) coating of surfaces is a promising infection control measure, though to date has not been tested against SARS-CoV-2. Methods: Virus stability was evaluated on TiO2- and TiO2–Ag (Ti:Ag atomic ratio 1:0.04)-coated 45 x 45 mm ceramic tiles. After coating the tiles were stored for 2–4 months before use. We tested the stability of both SARS-CoV-2 Spike… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…Their preliminary results showed that the genomic RNA of HCov-NL63 cells (a close genetic relative of SARS-CoV-2) were completely degraded after 30 min of UV exposure. Micochova et al [206] also evaluated the efficacy of light-activated TiO 2 and TiO 2 -Ag coatings prepared by spray gun on ceramic tiles, on the infectivity of SARS-CoV-2. They showed that the percentage of the infected SARS-CoV-2 after 1 h was only 15% on the illuminated TiO 2 coating compared to 80% on a polystyrene surface.…”
Section: Anti-sars-cov-2 Coatingsmentioning
confidence: 99%
“…Their preliminary results showed that the genomic RNA of HCov-NL63 cells (a close genetic relative of SARS-CoV-2) were completely degraded after 30 min of UV exposure. Micochova et al [206] also evaluated the efficacy of light-activated TiO 2 and TiO 2 -Ag coatings prepared by spray gun on ceramic tiles, on the infectivity of SARS-CoV-2. They showed that the percentage of the infected SARS-CoV-2 after 1 h was only 15% on the illuminated TiO 2 coating compared to 80% on a polystyrene surface.…”
Section: Anti-sars-cov-2 Coatingsmentioning
confidence: 99%
“…Disinfecting air, water, and surfaces with the photocatalytic reaction of LED-TiO 2 have been proven useful against many micro-organisms, including human coronavirus, and SARS coronavirus. It was found that the TiO 2 photocatalytic reaction for 20 min inactivated 99.9% of SARS-CoV-2 in aerosols and for 120 min it inactivated 99.9% of SARS-CoV-2 in liquids [126,127].…”
Section: Metal Oxide Nanoparticlesmentioning
confidence: 99%
“… 125 , 130 , 132 , 133 Zinc oxide and titanium dioxide coatings also show antiviral activity. 134 , 135 Antiviral heavy metals found in nutritional supplements may have some efficacy. 136 Quaternary ammonium compound coatings have attracted study.…”
Section: Coating and Impregnation Barriersmentioning
confidence: 99%